Efeito da relação oxigênio/combustível na microstrutura e propriedades de revestimentos quasicristalinos AlCuFeB e AlCoCu produzidos por HVOF - Feitosa, Francisco Riccelly Pereira (2018)
Discovered by Dan Shectman in 1982. Quasicrystals, ordered and aperiodic structures, are intermetallic compounds that have very different thermal and surface properties than conventional crystal structures. They are hard and brittle at room temperature, however because they have low thermal conductivity and low coefficient of friction, research suggests the application of these materials as hard coatings (high resistance to wear) and thermal barrier. The HVOF thermal spray process excels in obtaining thick and dense coatings. However, due to the large number of operational variables, a process optimization is still sought to improve the quality of the deposited quasicrystalline coatings. This work aimed to investigate the effects of O2 / fuel ratio on the microstructural integrity and properties of QC coatings. Quasicrystalline coatings on steel substrate were produced by HVOF (high velocity oxyfuel). The raw material was used twice in the production of powder: Al59,2Cu25,5Fe12,3B3 (icosahedral symmetry) with particle size ranging from 25-54 µm. Al65Co18Cu17 (decagonal symmetry) irregular geometry (polygonal and faceted) with piece size between 25-75 µm. The coatings were produced with five spray conditions from the variation in O2/kerosene ratio: 0.98 (fuel), 1.04 (fuel), 1.10 (stoichiometric), 1.16 (oxidant) and 1.22 (oxidant). The effect of the O2/kerosene ratio on the microstructure and coating properties was analyzed by X-ray diffraction, electron microscopy and x-ray photoelectron spectroscopy (XPS). The properties of hardness and modulus of elasticity were evaluated along the cross section of the coatings for each spray condition. In addition, the structural integrity of the coatings was monitored by the three-point flexural test coupled to piezoelectric sensors with the traction coating. The use of this technique, unprecedented in QC coatings, proved to be able to qualitatively determine the degradation of coatings under load. The coating Al59,2Cu25,5Fe12,3B3 produced with fuel ratio A5 (0.98), showed low porosity (<1.5%). This low porosity reflected in the hardness and modulus of elasticity, about 696.5 HV and 160.0 GPa respectively. Moreover, it was verified that the increase in the O2/fuel ratio was harmful, since it promoted a greater accumulation of defects in the microstructure of the coatings, impossible to be detected in the previous analyzes. This result was evident with the monitoring of the structural integrity (energy analysis of the D4 detail of the wavelet). The increase in the O2/kerosene ratio promoted a large increase in defects and discontinuities, which the energy for the coatings of AlCuFeB, A1 (1.22) oxidant ratio, is ten times smaller when compared to the A5 (0.98) fuel ratio. The porosity was 8.0% for the Al65Co18Cu17 coating, best result obtained with condition B3 (1.10), high value for coatings obtained by HVOF. The hardness and modulus of elasticity presented values of approximately 700 HV and 170 GPa respectively. Finally, the coatings produced with Al65Co18Cu17, regardless of the spray condition, presented high defects and discontinuities, a result of the low energy, verified through the monitoring technique with piezoelectric sensors.